PREVALENCE OF INTESTINAL HELMINTHIASIS IN THE RURAL AREA OF GILAN PROVINCE (CASPIAN LITTORAL)* - A.A Alemi; F. Arfaa (Tehran University of Medical Sciences, 1978)
Human infection with several intestinal helminthes especially soil-transmitted species is very prevalent in most parts of Iran (1, 2). Attempts made in the past decade by using systematic epidemiological surveys have indicated the true distribution and prevalence of these infections in most parts of the country. In this paper on soil-transmitted helminthes collected during a longitudinal health and morbidity survey in a rural area of Gilan province in the north of Iran and along the Caspian Sea are presented.